The analysis on forest farmers’ intention to participate in construction of the National Reserve Forest Project and its driving factors - Yang Song; Youzhi Wang; Gaocheng Hu (Scientific Reports)
Abstract The construction of the National Reserve Forest Project is the fundamental measure to alleviate the contradiction between national wood supply and demand and maintain national ecological security and wood security. This study analyzed the forest farmers’ intention to participate in the project and its driving factors. It provides a scientific basis for mobilizing forest farmers’ enthusiasm for continuous participation, improving their sense of gain, and realizing the established goals of constructing the National Reserve Forest Project. Based on the planned behavior theory, this study built a driving factor model regarding participation intention. From February to April 2022, forest farmers in the National Reserve Forest Project implementation area in Guizhou Province were selected as research objects for the questionnaire survey. A binary logistic regression model was used to verify and investigate the forest farmers’ participation intention and driving factors. Among the behavioral attitudes, income from participation in forest land transfer had a significant and positive correlation with concerns about forest use change. In the subjective norms, the study found a significant positive correlation between the degree of self-determination of forest farmers in participating in the project and the level of support from local government, village collectives, previously participating villagers, and family members. In perceived behavior control, qualification for project participation and acceptance of participation risk have a significant and positive correlation. The model based on planned behavior theory can well explain and predict the forest farmers’ intention to participate and driving factors. Currently, most forest farmers have a strong sense of intention to participate in the National Reserve Forest Project. Economic benefits, partners’ support in participation, guidance from superiors, and participation risk are important driving factors.